Nilai-Nilai Sosial yang Terkandung dalam Tradisi Bimbang Adat di Desa Suka Negeri - Jerlyanto; Adisel, Adisel; Satria, Irwan (IJOCE: Indonesia Journal of Civic Education, 2026)
This study aims to analyze the procession and social values embedded in the Bimbang Adat tradition in Suka Negeri Village, Air Nipis District, South Bengkulu Regency. This research employed a qualitative descriptive approach to gain an in-depth understanding of social phenomena. Data were collected through observation, interviews, and documentation involving traditional leaders, village officials, and local community members. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results indicate that the Bimbang Adat tradition consists of three main stages: preparation, implementation, and closing, each containing symbolic meanings and cultural values. The tradition embodies key social values such as mutual cooperation (gotong royong), social unity and solidarity, moral values, and responsibility. The value of mutual cooperation is particularly dominant, as reflected in the active participation of community members throughout the process. Furthermore, this tradition functions as a mechanism to strengthen social cohesion and maintain community harmony. Preservation efforts are carried out through cultural training, guidance from traditional leaders, and support from both the community and government. Therefore, the Bimbang Adat tradition serves not only as a cultural ritual but also as a medium for social education and preservation of local cultural values in the face of globalization.   Keywords: Bimbang Adat Tradition, Social Values, Mutual Cooperation, Local Culture, Cultural Preservation.